2015
DOI: 10.3171/2014.12.jns132840
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear line: a novel landmark for hearing preservation using the anterior petrosal approach

Abstract: T he anterior petrosal approach introduced by Kawase et al. was designed to enable wider and closer surgical exposure for treatment of ventral brainstem lesions. 1 The technique provides easy access to large sphenopetroclival meningiomas, dumbbell-shaped trigeminal schwannomas, and giant acoustic neuromas located in front of the brainstem and basilar trunk aneurysms. 5,7,9 The advantage of this technique is a lower possibility of postoperative hearing loss, vestibulopathy, and facial paresis in comparison with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…According to Wang et al, 14 the IAC can be found following posteriorly the GSPN from the facial hiatus to the geniculate ganglion, pro-ceeding with bone removal along the labyrinthine segment of the facial nerve. Kim et al 23 described the cochlear line as a key landmark to preserve the cochlea; the cochlear line was defined as a line drawn from the crossing point between the GSPN and the petrous ICA to the line drawn over the apex of the superior circumference of the dura of the internal auditory canal at a right angle. However, these methods place neurovascular structures at risk because their exposure is required.…”
Section: Discussionmentioning
confidence: 99%
“…According to Wang et al, 14 the IAC can be found following posteriorly the GSPN from the facial hiatus to the geniculate ganglion, pro-ceeding with bone removal along the labyrinthine segment of the facial nerve. Kim et al 23 described the cochlear line as a key landmark to preserve the cochlea; the cochlear line was defined as a line drawn from the crossing point between the GSPN and the petrous ICA to the line drawn over the apex of the superior circumference of the dura of the internal auditory canal at a right angle. However, these methods place neurovascular structures at risk because their exposure is required.…”
Section: Discussionmentioning
confidence: 99%
“…Another reason is that the necessity of the navigation system is questionable because the presence of several landmarks, including the cochlear line and digastric point, has been reported. 5 Anterior petrosectomy can be performed more efficiently using the cochlear line as a key landmark to preserve the cochlea. 5 Understanding the exact morphology of the temporal bone increases the success of maximal removal of the posterior wall of the IAC while minimizing morbidity secondary to violation of the bony labyrinth.…”
Section: Image Guidance For Skull Base Surgerymentioning
confidence: 99%
“…5 Anterior petrosectomy can be performed more efficiently using the cochlear line as a key landmark to preserve the cochlea. 5 Understanding the exact morphology of the temporal bone increases the success of maximal removal of the posterior wall of the IAC while minimizing morbidity secondary to violation of the bony labyrinth. 8 However, the high degree of interindividual variation in the relationships between surface structures and internal anatomy is a matter of some concern.…”
Section: Image Guidance For Skull Base Surgerymentioning
confidence: 99%
See 2 more Smart Citations